Problemy ohrany i zaŝity ličnyh (neimuŝestvennyh) prav intellektual'noj sobstvennosti posle smerti avtora : graždansko-pravovoj aspekt - Makoda, Volodimir Èvgenovič (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Given article expands the issues of copyright protection problems and the guarding of personal (nonproperty) intellectual property rights that occur after the author’s death. Author reports on the interpretation of the free access and intellectual property use; on the definition of compensated or uncompensated property use and setting limits, that would determine and exclude the certain differences. Also, author reveals the problems, that happen to the heirs of property (nonproperty) rights inherited after the author’s death
Keywords: intellectual property; property rights; property; commercial use of intellectual property; investors; protection of property rights; protection of nonproperty rights; copyright and related rights